Meningkatkan Literasi Siswa Desa Sukodono Kecamatan Dampit Kabupaten Malang Melalui Revitalisasi Perpustakaan Desa - Bramantyo Tri Asmoro; Devy Kumala Sari (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2020)
ABSTRACTThe rapid development in information technology have a postivie and negative impact. One of the negative impact is resulting in student’s low literacy. The Indonesian Government through the Ministry of Education and Culture issued Permendikbud Regulation No. 23 of 2015, which requires students to read books for 15 minutes before lessons begin with the aim of increasing student literacy. The effort to increase student literacy was also carried out by the Sukodono Village Government by creating a Village Library. The Village Library is managed by Youth Organization, but onits journey, Youth Organization is not optimal in managing it, so that the Village Library has not functioned properly. Community service activities were carried out in Sukodono Village, Dampit District, Malang Regency to increase students's interest in reading by revitalizing village libraries, namely adding library collections, involving stakeholders in library activities and promotion through singing and literary contest. Community service activities involve Youth Organization as the administrator of Village Library and schools at Sukodono Village, with the aim of creating sustainability towards efforts to increase student literacy. ABSTRAKSalah satu dampak negatif dari perkembangan teknologi informasi yang pesat adalah rendahnya minat baca siswa. Pemerintah melalui Kemendibud mengeluarkan aturan Permendikbud Nomor 23 Tahun 2015, yang mewajibkan siswa membaca buku selama 15 menit sebelum pelajaran dimulai dengan tujuan untuk meningkatkan literasi siswa. Upaya peningkatan literasi siswa juga dilakukan oleh Pemerintah Desa Sukodono dengan membuat Perpustakaan Desa. Perpustakaan Desa dikelola oleh Karang Taruna, namun dalam perjalanannya Karang Taruna tidak maksimal dalam mengelola sehingga perpustakaan desa belum berfungsi sebagaimana mestinya. Kegiatan pengabdian kepada masyarakat ini dilakukan di Desa Sukodono, Kecamatan Dampit, Kabupaten Malang untuk meningkatkan minat baca siswa dengan melakukan revitalisasi perpustakaan desa, yaitu penambahan koleksi pustaka, melibatkan stakeholder dalam kegiatan dan promosi perpustakaan melalui lomba. Kegiatan pengabdian melibatkan Karang Taruna sebagai pengelola perpustakaan desa dan sekolah dengan tujuan untuk menciptakan keberlanjutan terhadap upaya peningkatan literasi siswa.